Analysis of Efforts to Maintain the Performance of the Steam Bottle Through Care Water Kettle to Use Guard Element Chemical on Water Bottle in SS. Triputra - Markus Yando; Suhartini Suhartini; Desamen Simatupang; Angelina Sabila Janna (Journal of Accounting and Finance Management, 2022)
This study focuses on the problems that occur on the SS ship. TRIPUTRA, when the author carried out PRALA, namely there was an error in the report on the results of the chemical analysis of boiler water, allegedly due to mistaker in the water chemistry experiment process kettle which causes the boiler water specifications, do not match those determined based on the manual book. Research purposes This is to find the proper and correct boiler water chemistry experiment procedures, better understand the relationship between chemical elements in boiler water with long-term hazards that can occur, and provide socialization and knowledge about material injection chemistry in each engine room crew. The method used is descriptive qualitative, which aims to make a description or describe systematically the background of the problems that occur in the SS. TRIPUTRA, so you can obtain an accurate and systematic picture related to the events being investigated. Data collection techniques are observation, interviews, documentation, and literature study. The results showed that an error causes high levels of hydrazine and the excess hardness in the boiler water in the process chemistry experiment and care kettle water which is human error.